Mary Anne's Makeover - Martin, Ann M. (New York Scholastic Inc., 1993)
When Mary Anne sees a picture of a haircut that she really likes, the Baby-sitters don't pay much attention to it. They like good old Mary Anne just the way she is. Mary Anne gets a new haircut, some new clothes, and a little makeup. Now she can't wait for the Baby-sitters to see her. But the Baby-sitters can't believe what she has done, and that makes Mary Anne mad.
Include Illustrations
Keywords: Clubs -- Friendship